2017
DOI: 10.15414/jmbfs.2017.6.6.1264-1268
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR IDENTIFICATION AND ANTIBIOGRAM OF Enterococcus spp. ISOLATED ON ENTEROCOCCUS SELECTIVE DIFFERENTIAL (ESD) MEDIA FROM MEAT, MEAT PRODUCTS AND SEAFOOD IN LIBYA

Abstract: Keywords: 16S rDNA, antibiogram, enterococci, food, Libya

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
8
1
Order By: Relevance
“…This contradicts the study by Mus et al (2017) where E. faecalis 29 (26.6%), which carries one of the virulence-associated determinants, were simultaneously resistant to a minimum of one antibiotic. All enterococci strains screened for their antibiotic-resistant profiles revealed high multiresistance phenotype (Naas et al, 2017), which was contradicted by the findings from this study. Species-specific primers by Mus et al (2017) revealed E. faecalis as the predominant Enterococcus species carrying one or more virulence-associated determinants.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This contradicts the study by Mus et al (2017) where E. faecalis 29 (26.6%), which carries one of the virulence-associated determinants, were simultaneously resistant to a minimum of one antibiotic. All enterococci strains screened for their antibiotic-resistant profiles revealed high multiresistance phenotype (Naas et al, 2017), which was contradicted by the findings from this study. Species-specific primers by Mus et al (2017) revealed E. faecalis as the predominant Enterococcus species carrying one or more virulence-associated determinants.…”
Section: Discussioncontrasting
confidence: 97%
“…The prevalence of E. faecalis from cultured Indian prawn at Damietta governorate, Egypt, was 7% (El-Far et al, 2015), which was similar to the findings of this study. However, higher prevalence within the range of 16.7–74.1% has been documented previously (Koluman et al, 2009; Jamet et al, 2012; Jahan et al, 2013; Pesavento et al, 2014; Boss et al, 2016; Chajecka-Wierzchowska et al, 2016; Mus et al, 2017; Naas et al, 2017).…”
Section: Discussionmentioning
confidence: 54%
“…Generally, meat can be prone to microbial spoilage and can harbour a wide variety of foodborne and zoonotic agents, such as Campylobacter spp., Staphylococcus aureus, and Enterococcus spp. All these pathogens can be harboured within the gastrointestinal tract of food-producing animals and, hence, contamination to meat during the processing at an abattoir, with subsequent human illnesses, is a rational expectation (Naas et al 2017;Premarathne et al 2017;Tyson et al 2018). Several other bacterial zoonotic pathogens may exist and have been described already in different camel samples such as Salmonella, the Shiga toxin producing E. coli (O157:H7 and other serotypes), Listeria and Clostridium difficile (Bosilevac et al 2015;Esfandiari et al 2015;Stipetic et al 2016).…”
mentioning
confidence: 99%
“…Enterococci are, Gram-positive lactic acid bacteria, ubiquitous in the environment (in the soil, on plants, and in water), considered as common commensals of the gastrointestinal tract of mammals, birds, insects, and reptiles and can be found in foods, especially those of animal origin (Tyson et al 2018). Enterococcus faecalis and Enterococcus faecium, have recently emerged as opportunistic pathogens and ranked third among the leading causes of nosocomial infection including endocarditis, urinary tract infections, central nervous system, intra-abdominal and pelvic infections (Naas et al 2017). Enterococci have intrinsic resistance to several antibiotics and have the ability to exchange the genetic information between themselves and to non-pathogenic organisms by means of plasmids and transposon (Rozanska et al 2015).…”
mentioning
confidence: 99%
“…Zoonotic microbes, such as Enterococcus sp., Staphylococcus aureus, and Campylobacter spp., and many other foodborne pathogens contaminate meat. The gastrointestinal tract of food-producing animals can harbor many of these pathogens, which can contaminate meat during processing at an abattoir, resulting in subsequent human illnesses [15]. The Kingdom of Saudi Arabia is projected to be the largest consumer of camel meat in the Arabian Gulf region, and the demand for camel meat is expected to grow as the population, number of visitors, and consumer preference for fresh camel meat increase.…”
Section: Introductionmentioning
confidence: 99%